Integrated farming system model for livelihood security and doubling the Income of small-and marginal-farmers under changing climate scenario - Behera, U K; Bhargabhi, B; Meena, S L; Singh, Raj; Singh, V K (Indian Farming, 2018)
The entire philosophy of integrated farming system revolvesround better utilization of time, money, resources and family labourers of farm families. The farm family gets scope for gainful employment round the year, thereby ensuring good income and better standard of living. It is high time that the scientists, administrators and planners should think on such lines and provide adequate facilities and encouragement to the small and marginal farmers and rural youth togo ahead with the integrated farmingsystems with a sense of commitment for the rural development in totality.